2000
DOI: 10.1177/089826430001200104
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Race and Health-Related Factors on Naming and Memory

Abstract: The racial differences found in test performance may reflect differences in cultural appropriateness of the material rather than differences in ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 62 publications
3
49
3
Order By: Relevance
“…This accelerated cognitive aging hypothesis needs to be tested empirically, but may account for differences in mean levels of cognitive functioning as more cross-cultural analyses are performed. Cross-cultural differences found in test performance may reflect differences in cultural appropriateness of the material rather than differences in ability (Whitfield et al, 2000). When measures are culturally sensitive, models of cognitive aging for European-Americans may need to be modified if they are to apply to other groups (Whitfield et al, 1997(Whitfield et al, , 2000Whitfield & Willis, 1998).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This accelerated cognitive aging hypothesis needs to be tested empirically, but may account for differences in mean levels of cognitive functioning as more cross-cultural analyses are performed. Cross-cultural differences found in test performance may reflect differences in cultural appropriateness of the material rather than differences in ability (Whitfield et al, 2000). When measures are culturally sensitive, models of cognitive aging for European-Americans may need to be modified if they are to apply to other groups (Whitfield et al, 1997(Whitfield et al, , 2000Whitfield & Willis, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, if ethnic differences exist, they are not entirely due to lack of competence but due to differences in practices, attitudes, beliefs, and historical legacies that are aspects of individual ethnic=cultural groups that subsequently impact performance. Other variables such as health status and social factors (Whitfield et al, 2000;Whitfield & Willis, 1998) have been shown to impact performance on measures of cognitive functioning among African Americans.…”
mentioning
confidence: 98%
“…For some exposures, there has been much more research on physical health outcomes, such as cardiovascular conditions. Although this is not a focus of this review, we must acknowledge prior work finding a strong link between cognitive health and physical health (Whitfield et al 2000), especially vascular functioning. (Snowdon et al 1997;Cerhan et al 1998;Kilander et al 1998;de la Torre 2000;Gregg et al 2000;Hachinski and Munoz 2000;Hébert et al 2000;Fontbonne et al 2001) Recent work adopting a "brain at risk" approach highlights the value of considering neuropathological processes in the context of physical health, in particular cardiovascular health (Hachinski 2007), consistent with a broader lifecourse perspective on neurodegenerative diseases (Whalley et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…While it is likely that numerous mediating factors (e.g., education, health conditions, and socioeconomic status, etc.) account for the lower performance of African Americans on tests of cognitive ability and functioning, several researchers have noted that such demographic and health factors are infrequently considered in many existing published studies exploring racial group differences in cognition (Whitfield, Fillenbaum, Pieper, Albert, Berkman, Blazer, Rowe, & Seeman, 2000;IzquierdoRorrera & Waldstein, 2002;Zsembik & Peek, 2001). …”
mentioning
confidence: 99%